2022
DOI: 10.3389/fphar.2022.856410
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea Purpurea For the Long-Term Prevention of Viral Respiratory Tract Infections During Covid-19 Pandemic: A Randomized, Open, Controlled, Exploratory Clinical Study

Abstract: SARS-CoV-2 vaccination is effective in preventing severe Covid-19, but efficacy in reducing viral load and transmission wanes over time. In addition, the emergence of novel SARS-CoV-2 variants increases the threat of uncontrolled dissemination and additional antiviral therapies are urgently needed for effective containment. In previous in vitro studies Echinacea purpurea demonstrated strong antiviral activity against enveloped viruses, including SARS-CoV-2. In this study, we examined the potential of Echinacea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…As of October 1, 2022, 119 preprints (78.3%) had been published in a scientific, peer-reviewed journal (Figure 2 and eTable 3 in Supplement 1). Two preprints were published in a single journal publication . The median time to publication was 186 days (range, 17-407 days).…”
Section: Resultsmentioning
confidence: 99%
“…As of October 1, 2022, 119 preprints (78.3%) had been published in a scientific, peer-reviewed journal (Figure 2 and eTable 3 in Supplement 1). Two preprints were published in a single journal publication . The median time to publication was 186 days (range, 17-407 days).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the strongest antiviral effects were found when epithelial cells were in direct contact with EF indicating immediate treatment or prophylactic benefits rather than with post-exposure of cells ( 8 , 12 ). In randomized, double-blind placebo-controlled trials, the prophylactic use of EF significantly reduced the incidence of laboratory-confirmed viral RTIs and was non-inferior to the placebo in terms of safety ( 13 15 ). Similar results were found for Echinaforce Hot Drink ® which was non-inferior to oseltamivir in the treatment of ILI.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized, controlled clinical studies (RCTs) have demonstrated efficacy for a 65% hydroethanolic extract from Echinacea purpurea herb and roots (Echinaforce ® [EF]) in the prevention and the treatment of RTIs including secondary complications ( 13 17 ). Five months of EF prevention during the COVID-19 pandemic (2020–2021) reduced enveloped virus infections by 43.2%, coronavirus infections by 48.3%, and SARS-CoV-2 by 63.1% ( p < 0.05) ( 15 ). Moreover, Nicolussi et al found significantly reduced enveloped virus infections in adults and children and >98% decreased viral loads with increased EF dosages used for the acute treatment ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments with human macrophages found that fresh-pressed juice and dried juice from the aerial parts of E. purpurea stimulated the production of cytokines including IL-1, IL-10, and TNF-α [ 54 ]. In addition, evidence pointed out the effective activity of E. purpurea towards Coronavirus disease 2019 (COVID-19) in an organotypic cell culture model [ 55 , 56 , 57 ].…”
Section: Most Commonly Used Medicinal Plants For the Treatment Of The...mentioning
confidence: 99%